2009
DOI: 10.1681/asn.2008060628
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and Serum Amyloid A Synergy Mediates Angiotensin II–Induced Muscle Wasting

Abstract: Animal studies suggest that increased levels of circulating angiotensin II (AngII) could contribute to the loss of lean body mass in chronic kidney disease, but the mechanism by which this occurs is unclear. Here, AngII infusion increased circulating IL-6 and its hepatic production in wild-type mice, suggesting that AngII-induced inflammation may trigger muscle loss. AngII infusion also stimulated the suppressor of cytokine signaling (SOCS3) in muscle, which led to loss of insulin receptor substrate 1 (IRS-1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
250
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(264 citation statements)
references
References 41 publications
11
250
1
2
Order By: Relevance
“…mediated by intermediate molecules, including cytokines and glucocorticoids (4,18), which is consistent with the fact that adult muscle fibers express little to no Ang II receptors (18,19). However, we demonstrated recently that Ang II also acts directly on skeletal muscle via its effects on satellite cells (19).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…mediated by intermediate molecules, including cytokines and glucocorticoids (4,18), which is consistent with the fact that adult muscle fibers express little to no Ang II receptors (18,19). However, we demonstrated recently that Ang II also acts directly on skeletal muscle via its effects on satellite cells (19).…”
supporting
confidence: 83%
“…Ang (1-7), mainly produced from Ang II by ACE2 and signaling through the Mas receptor, has been reported to regulate skeletal muscle insulin sensitivity (34,35), decrease fibrosis, and improve muscle function in a mouse model of muscle dystrophy (36). It has been shown by us (2-9) and by others (10 -12) (4,18), which is consistent with the fact that adult muscle fibers express little to no Ang II receptors (18,19). However, recently, we discovered that satellite cells express the AT1R and that Ang II acts via these receptors to prevent satellite cell proliferation and suppress muscle regeneration (19).…”
Section: Discussionmentioning
confidence: 93%
“…RT-PCR-RT-PCR was performed as described (15,16); the relative gene expression was calculated from cycle threshold values using 18 S RNA or GAPDH as an internal control (C t ; relative expression ϭ 2 (sample Ct Ϫ 18 S Ct)…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a synergism between IL-6 and other catabolic substances that produce muscle loss have recently been demonstrated. First, Zhang et al (26) demonstrated a previously unrecognized role for serum amyloid A in acting synergistically with IL-6 to impair insulin/ IGF-1 signaling by increasing SOCS3 transcription, which results in muscle proteolysis (Figure 2A). They proposed that angiotensin II may stimulate an interaction between the liver and the skeletal muscle because the liver becomes the major source of IL-6 and serum amyloid A.…”
Section: Inflammation Exacerbates the Effects Of Protein-energy Wastingmentioning
confidence: 99%